A constitutional economics perspective on soft paternalism - Jan Schnellenbach (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik und Ordnungsökonomik, 2015)
Using a framework that distinguishes short-term consumer preferences, individual reflective preferences and political preferences, we discuss from a constitutional economics perspective whether individuals find it in their common constitutional interest to endow representatives and bureaucrats with the competence to impose soft paternalist policies. The focus is specifically on soft paternalist policies, because these often work with non-transparent 'nudges' that are considered as manipulative in some contributions to the literature. We show that those soft paternalist policies that are manipulative indeed collide with three criteria of consumer sovereignty, reflective sovereignty and citizen sovereignty that can be argued to represent common constitutional interest of citizens. On the other hand, we argue that the set of paternalist policies that is deemed acceptable on the constitutional level is restricted to non-manipulative instruments, and their application as government policies is limited to cases with stable and very homogenous preferences. However, we also argue that competitive markets are capable of supplying many mechanisms that allow individuals to cope with problems in their decision-making processes on a private level. – – In diesem Papier wird untersucht, ob und in welchem Umfang paternalistische politische Maßnahmen gerechtfertigt werden können, sofern diese nicht mit klaren Regeln arbeiten, sondern Schwachpunkte individueller Entscheidungsprozesse nutzen, wie sie aus der Verhaltensökonomik bekannt sind. Die zur Beurteilung herangezogenen Kriterien sind aus der verfassungsökonomischen Theorie abgeleitet. Im Ergebnis zeigt sich, dass der sogenannte 'weiche' Paternalismus nur in sehr seltenen Fällen verallgemeinerbaren Interessen der Bürger entspricht, nämlich dann, wenn seine Instrumente vollständig transparent und nicht manipulativ sind, sowie die Entscheidungsautonomie des Einzelnen gewahrt bleibt.
Keywords: D11; D18; D63; D83; H11; Z18; 330; nudge; biases; autonomy; consumer sovereignty; reflective preferences; behavioural policies